(3hUa QMdI Edi GdMHTI SfI (B1052s - (3GdMSf Hf CMeO GdMjej GdTHGej, GdbGVj TQa GdOjfs ((3CMeO Hf YHO Gddg Hf CMeO Hf YHO Gddg s)
(3ChdgG (B:s
(3hHYO aEfg SCdfi ef hLg Edi Ced GdESYGa s
(3BNQgG (B:s
(3HCMSf eG jQhjg GdEfSGf hjfWdb Hg GddSGf s
(3HgG fXGe GdJYbjHIs
(3cJHJ HfGA Ydi CeQ GdeJhcd Ydi Gddg GSeGYjd Hf GdbGSe Hf eMeOs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3NOGHNT (B(2886) s
Keywords: (3GdLZQGajG h GdHdOGfs